Perspectives of stakeholders on onboard training: A thematic analysis of qualitative interviews - Thammawan Phanphichit; Inga Bartusevičienė (Journal of International Maritime Safety, Environmental Affairs, and Shipping)
The training and education of seafarers have evolved significantly with the establishment of the International Maritime Organization (IMO) and the adoption of International Convention on Standards of Training, Certification and Watchkeeping for Seafarers (STCW). This paper explores maritime industry key stakeholders’ perspectives on onboard training (OBT) focusing on its benefits, curriculum, and challenges. The thematic analysis of the opinions of representatives of key stakeholders highlighted the critical role of OBT in providing real-world experience, applying theoretical knowledge in practice, and gaining cultural insights essential for maritime cadets’ professional growth. Some obstacles related to financial constraints of shipping companies, common ship activities, living conditions on board, unexpected weather conditions, regulatory inconsistencies, and characteristics of curriculum, such as trainers’ competencies, number of trainers on board, different implementation of OBT by different companies were revealed. The respondents agreed that the traditional 12-month OBT period is necessary, however proper integration of technological advancements in achieving competences with harmonized international regulations, updated curriculum, and enhanced stakeholder collaboration can be helpful to reduce the duration of OBT. Further research should identify competences to be developed through integration of technologies including simulator training.